Pengaruh Process-Oriented Guided-Inquiry Learning (POGIL) Terhadap Kemampuan Problem Solving Siswa - Ivan Ashif Ardhana (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[THE EFFECT OF PROCESS-ORIENTED GUIDED-INQUIRY LEARNING (POGIL) TOWARD STUDENTS’ PROBLEM SOLVING SKILLS]. The aim of this research is to investigate the different impacts of Process-Oriented Guided-Inquiry Learning (POGIL) and verification as a learning approach at senior high school students’ problem solving ability grade XI program IPA on acid-base topic. The research design used was quasi experimental. Hypothesis testing uses a t-test with 5% significance utilizing SPSS 21 program for windows. Results show that (1) there is a significant difference in students’ problem solving ability that is taught by POGIL approach and verification, and (2) students that are taught by POGIL approach give better answer’s pattern than students that are taught by verification approach. According to the research result, POGIL could be well promoted learning model to developing problem solving skill on acid-base topics. This result does imply to the next similar research that appropriate exploration of problem solving ability on another contextual chemistry topic such as rate of reaction, chemical equilibrium, and colligative properties. Exploration about metacognition involvement on POGIL also the other implication of this research result that can be deeply analyzed.